Enhancing EFL writing skills for adult Deaf and hard of hearing individuals - Chomicz, Marta (Frontiers in Education, 2025)
The paper examines how Deaf and hard of hearing (D/HH) learners use information technology to develop English as a Foreign Language (EFL) writing skills. Conducted during two EU-funded summer schools, one in Italy and one in Poland, the research explores how internet tools like Google Translate, ChatGPT, and online dictionaries affect writing quality and confidence among 18 adult D/HH participants. The findings indicate that participants perceived these tools as improving vocabulary, grammar, coherence, and writing confidence. Moreover, the study highlights the creative strategies D/HH learners use to overcome linguistic challenges, such as employing simple and direct language, imaginative storytelling, and using visual imagery. Participants demonstrated resourcefulness in conveying complex ideas despite limitations in vocabulary and grammar, even when writing without technology. With the aid of internet tools, these strategies were further enhanced, helping to improve the clarity and structure of their texts. However, the research acknowledges limitations of relying heavily on technology, as it may limit opportunities for independent language growth. The study emphasizes the need for a balanced approach that integrates both technology and traditional methods to foster comprehensive EFL skill development.